问题 解答题
递等式计算(怎样简便就怎么计算)
1
3
÷(
2
3
-
2
5

1
3
×
3
4
÷(
3
4
-
5
12

6
7
×
6
5
-
6
7
÷5
3
10
-
3
10
÷6
36
48
49
×
1
4

7
4
÷(
2
3
+
1
2
)×
4
5
答案

(1)

1
3
÷(
2
3
-
2
5

=

1
3
÷
4
15

=1

1
4

(2)

1
3
×
3
4
÷(
3
4
-
5
12

=

1
3
×
3
4
÷
1
3

=

1
4
÷
1
3

=

3
4

(3)

6
7
×
6
5
-
6
7
÷5

=(

6
5
-
1
5
)×
6
7

=1×

6
7

=

6
7

(4)6÷

3
10
-
3
10
÷6

=20-1.8

=18.2;

(5)36

48
49
×
1
4

=36×

1
4
+
48
49
×
1
4

=9+

12
49

=9

12
49

(6)

7
4
÷(
2
3
+
1
2
)×
4
5

=

7
4
÷
7
6
×
4
5

=

3
2
×
4
5

=1

1
5

填空题
多项选择题